1994
DOI: 10.3354/meps104109
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-term hypoxia exposure on the energy metabolism of Solea solea. I. Critical 02 levels for aerobic and anaerobic metabolism

Abstract: Long-term hypoxia is a general phenomenon on the Italian Adriatic coastline, and is mainly caused by continuous eutrophication. The sensitivity of sole Solea solea to long-term hypoxia was investigated. Healthy S. solea obtained from trawls were kept at l g°C in aquana for at least 2 mo. The fish were exposed to hypoxia after a preacclimation penod of 30 h at normoxia Oxygen levels dunng normoxla were kept constant at 80% air saturahon (16.6 kPa, 6 . 4 mg I-' OZ); during hypoxia oxygen levels were set at 60, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 19 publications
9
41
0
Order By: Relevance
“…The increase in plasma Cl -may be related to HCO 3 -decrease, as gill acid-base flux (H + and HCO 3 -) is usually coupled to ion exchanges (Cl -and Na + ). Marked increase in plasma lactate showed that fish resorted to anaerobic metabolism within 4 h, as has previously been observed in turbot under similar hypoxic conditions and in another flat fish species, sole (Solea solea) (Dalla Via et al, 1998;Van den Thillart et al, 1994). Survival was over 95% at the end of the 12-h test, which is in agreement with the survival challenge test results.…”
Section: Discussionsupporting
confidence: 79%
“…The increase in plasma Cl -may be related to HCO 3 -decrease, as gill acid-base flux (H + and HCO 3 -) is usually coupled to ion exchanges (Cl -and Na + ). Marked increase in plasma lactate showed that fish resorted to anaerobic metabolism within 4 h, as has previously been observed in turbot under similar hypoxic conditions and in another flat fish species, sole (Solea solea) (Dalla Via et al, 1998;Van den Thillart et al, 1994). Survival was over 95% at the end of the 12-h test, which is in agreement with the survival challenge test results.…”
Section: Discussionsupporting
confidence: 79%
“…A is the allometric exponent describing the relationship between metabolic rate and body mass (0.8: van den Thillart et al 1994). Background oxygen consumption by micro-organisms was routinely assessed before the fish was transferred into the chamber by recording the oxygen consumption of an empty respirometer.…”
Section: Methodsmentioning
confidence: 99%
“…Parallel laboratory experiments showed that in 30% air saturated water, both flatfish species were already constrained and displayed negative mean growth (Petersen & Pihl 1995). Because of this relatively restricted behavioural repertoire, flatfish are more liable to be exposed to environment-mediated changes in their biological performance (Duthie 1982, van den Thillart et al 1994. The aim of the present study was to assess the influence of ambient temperature and oxygenation on the metabolism and cardiovascular physiology of a poorly studied but economically important flatfish species, the common sole Solea Influence of ambient oxygenation and temperature on metabolic scope and scope for heart rate in the common sole Solea solea ABSTRACT: The objective of this study was to quantify the constraints exerted by temperature and oxygenation on both metabolic scope and scope for heart rate of the common sole Solea solea.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a P c value between 8.6 and 6.7 kPa was derived from aerobic-anaerobic transition or oxygen consumption data in the burrowing marine teleost Lumpenus lampretaeformis (Pelster et al, 1988). In the flatfish Solea solea, the P ranged between 4.0 and 2.4 kPa (van den c Thillart et al, 1994), while the P was 6.7 kPa in Octopus vulgaris (Wells and Wells, c 1995), and between 7.0 and 4.0 kPa in the bivalve Scapharca inaequivalvis (van den Thillart et al, 1992). In some animals, for example the toad Bufo marinus (Portner et al, 1991b), a transient increase in oxygen consumption has been reported to set in at the P c when anaerobic metabolism starts.…”
Section: Anaerobic Metabolism and The Critical P Omentioning
confidence: 99%
“…phosphocreatine, phospho-L-arginine) and / or by ATP production through anaerobic metabolism (Portner and Grieshaber, 1993;van den Thillart et al, 1994). Nonetheless, survival under hypoxic conditions is time limited since eventually the energy status becomes impaired, reflected by a drop in the cellular Gibb's freë energy of ATP hydrolysis to possibly limiting levels (Kammermeier, 1987;.…”
Section: Introductionmentioning
confidence: 99%